Variation in the fibroblast growth factor 23 (FGF23) gene associates with serum FGF23 and bone strength in infants - Enlund-Cerullo, Maria; Holmlund-Suila, Elisa; Valkama, Saara; Hauta-alus, Helena; Rosendahl, Jenni; Andersson, Sture; Pekkinen, Minna; Mäkitie, Outi (Frontiers in Genetics, 2023)
Introduction: Effects of genetic variation of Fibroblast Growth Factor 23 (FGF23) are unclear. This study explores associations of single nucleotide polymorphisms (SNPs) of FGF23 with phosphate and vitamin D metabolism and bone strength in early childhood. Methods: The study is part of the Vitamin D intervention in infants (VIDI) trial (2013-2016), in which healthy term infants of mothers of Northern European origin, received Vitamin D3 supplementation of 10 or 30 g/day from 2 weeks to 24 months of age (ClinicalTrials.gov NCT01723852). Intact and C-terminal FGF23 (cFGF23), 25-hydroxyvitamin D (25-OHD), parathyroid hormone, phosphate and peripheral quantitative computed tomography (pQCT)-derived bone strength parameters were analyzed at 12 and 24 months. The study included 622 VIDI-participants with genotyping data on FGF23 SNPs rs7955866, rs11063112 and rs13312770. Results: Rs7955866 minor allele-homozygotes had lowest cFGF23 at both time-points (mixed model for repeated measurements, pvariant=0.009). Minor alleles of rs11063112 associated with greater age-related decrease in phosphate (pinteraction=0.038) from 12 to 24 months. Heterozygotes of rs13312770 had greatest total bone mineral content (Total BMC), cross sectional area (Total CSA) and polar moment of inertia (PMI) at 24 months (ANOVA p=0.005, 0.037 and 0.036 respectively). Rs13312770 minor alleles associated with greater increase of Total BMC, but smaller increase of Total CSA and PMI, during follow-up (pinteraction <0.001, 0.043 and 0.012, respectively). FGF23 genotype did not modify 25-OHD. Conclusions: The study finds that genetic variation of FGF23 modifies cFGF23, phosphate and pQCT-derived bone strength parameters from 12 to 24 months of age. These findings potentially promote understanding of the regulation of FGF23 and its role in bone metabolism and temporal changes thereof during early childhood.